Handling of Juvenile Brawl Crimes through Criminal Law Policy in Medan City - Rahul Ardian Fikri; Mhd Azhali Siregar; Muhammad Juang Rambe; Nabilah Syaharani (JURNAL HUKUM SEHASEN, 2024)
This study focuses on criminal law policies in dealing with criminal acts of assault or brawls (tawuran) caused by juvenile delinquency in Medan City. Student brawls have become a trend among teenagers, especially at the high school level and equivalent, which are triggered by various internal and external factors, including family influences, school environment, and social pressure. This study aims to determine the legal basis governing criminal acts of brawls, the factors causing brawl behavior among students, and efforts to overcome them made by law enforcement, the community, and schools. The approach used in this study is a qualitative descriptive method, which includes data collection through interviews and direct observation at the Medan Police Headquarters. The results of the study indicate that factors such as frustration, emotional disturbances, and environmental influences contribute to juvenile delinquency behavior that leads to brawls. This study emphasizes the importance of the Restorative Justice approach in resolving brawl cases and proposes the need for collaboration between educational institutions, law enforcement, and the community to prevent and handle these cases effectively.